Fertility treatment and breast-cancer incidence: meta-analysis. Issue 1 (9th February 2022) - Cullinane, Carolyn; Gillan, Hannah; Geraghty, James; Evoy, Denis; Rothwell, Jane; McCartan, Damian; McDermott, Enda W.; Prichard, Ruth S.
Abstract: Background: The significance of exogenous hormone manipulation as part of fertility treatment and its relationship to the development of breast cancer remains uncertain. Several historical reviews have been performed with conflicting results. This study is an updated meta-analysis to determine whether there is a causal relationship between different fertility treatments and breast cancer. Methods: The study report is based on the guidelines of PRISMA and Meta-Analysis of Observational Studies in Epidemiology. Studies published within the last 20 years were included to reflect up to date in vitro fertilization (IVF) practice. This study was prospectively registered on PROSPERO on 07/04/2021, registration identification CRD42021247706. The primary outcome of the study was to determine whether there is an increased incidence of breast cancer in women treated with hormonal fertility treatment. The secondary outcomes were to determine whether fertility treatments were individually associated with excess breast-cancer risk. Results: Overall, 25 studies, including 617 479 participants, were eligible for inclusion. There was no significant breast-cancer risk association with fertility treatment (compared with general and subfertility reference groups). Summary odds ratio of all included studies was 0.97 (95 per cent c.i. 0.90 to 1.04). Women who received six or more IVF cycles did not have an increased risk of breast cancer. Similarly, there was no excess breast-cancer risk associated with clomiphene, human chorionic gonadotropin, gonadotropin analogues and progesterone when examined individually. Comparably, there was no significant association between fertility treatment and excess breast-cancer risk in patients with more than 10 years' follow-up. Summary odds ratio was 0.97 (95 per cent c.i. 0.85 to 1.12). Conclusion: This meta-analysis did not find a significant association between fertility treatments and excess breast-cancer risk. Women considering IVF should be informed that it does not appear to increase breast-cancer risk. Abstract : This meta-analysis of 25 studies published within the last 20 years did not find a significant association between fertility treatments and excess breast-cancer risk. Women considering IVF should be informed that IVF does not appear to increase breast-cancer risk.